2020
DOI: 10.1101/2020.05.11.20097790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19: a retrospective cohort study with focus on the over-80s and hospital-onset disease

Abstract: Objectives: To describe the presenting features and outcomes of patients with COVID-19 in a UK hospital, with a focus on those patients over 80 years and patients with hospital onset infection. Design: Retrospective cohort study with data extracted from the electronic records of patients with PCR-confirmed COVID-19 admitted to our institution. Setting: Suburban general hospital serving the most populous London borough. Participants: The first 450 inpatients admitted to our hospital with swab-confirmed C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 11 publications
4
25
0
Order By: Relevance
“…Our findings are also consistent with previously reported associations between high mortality and older age 15,20‐22 . While we did not find associations between mortality and dyspnoea, 23 cardiovascular disease 24 or male gender 25 reported elsewhere, our population represents severe disease admitted to secondary care with a high overall mortality of 65%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are also consistent with previously reported associations between high mortality and older age 15,20‐22 . While we did not find associations between mortality and dyspnoea, 23 cardiovascular disease 24 or male gender 25 reported elsewhere, our population represents severe disease admitted to secondary care with a high overall mortality of 65%.…”
Section: Discussionsupporting
confidence: 93%
“…Data were collected retrospectively from the electronic patient record. Further information is available here 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings add to emerging reports quantifying the relationship between frailty and mortality in COVID-19. In another London hospitalised cohort, crude deaths in COVID-19 were higher in patients who were frailer (median Clinical Frailty Scale score of 5 versus 4, p = 0.01) [13]. Other UK case series have shown that patients who died without ventilatory support had a median Clinical Frailty Scale score of 7 [14].…”
Section: Discussionmentioning
confidence: 91%
“…16,28,30,38,39 After accounting for potential overlapping patient cohorts in these smaller studies, we identified 20 unique cohorts encompassing 13,137 patients with available kidney disease-related information. 4,[12][13][14][15][19][20][21][22][23][24]26,30,32,33,[35][36][37][38][39] Of these 20 cohorts included in the statistical analysis, 13 were from China, 1 was from Korea, 3 were from the United States, and 3 were from Europe. The quality of peer-reviewed studies and preprint studies were similar (Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%